Countering Corruption: The Experience of the United Arab (pat 2) - Frantsuz, A.; Liashchenko, M.; Француз, Анатолій Йосипович (Університет «КРОК», 2018)
The article examines the experience of combating corruption in the United Arab Emirates on the background of socio-economic transformations that took place in that country during the years 1971-2017

У статті досліджено досвід боротьби з корупцією в Об’єднаних Арабських Еміратах на тлі соціально-економічних перетворень, що відбулися в цій країні протягом 1971-2017 років
Keywords: corruption; fi ght against corruption in the United Arab Emirates; anti-corruption legis-lation; bribery; nepotism; корупція; боротьба з корупцією в ОАЕ; антикорупційне законодавство; хабарництво; непотизм